2017
DOI: 10.1002/acm2.12065
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of intra‐voxel incoherent motion measurement in diffusion‐weighted imaging of breast cancer

Abstract: PurposeThe purpose of this study was to optimize intra‐voxel incoherent motion (IVIM) measurement in diffusion‐weighted imaging (DWI) of breast cancer by separating perfusion and diffusion effects through the determination of an optimal threshold b‐value, thus benign and cancerous breast tissues can be accurately differentiated using IVIM‐derived diffusion and perfusion parameters.Materials and MethodsTwenty‐eight patients, with biopsy‐confirmed breast cancers, were studied with a 3T MRI scanner, using T1‐weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Studies discovered a considerable vascular influence in both DCIS and invasive breast lesions (Fig. 11) [18].
Fig.
…”
Section: What Are the New Developments?mentioning
confidence: 99%
“…Studies discovered a considerable vascular influence in both DCIS and invasive breast lesions (Fig. 11) [18].
Fig.
…”
Section: What Are the New Developments?mentioning
confidence: 99%
“…This multi-step process requires a b-value threshold to be selected, and several studies have demonstrated the importance of choosing an appropriate threshold (22,39). However, it was also found that the threshold is dependent on the organs, with values ranging from 20 s/mm 2 in the healthy liver (19) to 300 s/mm 2 in breast cancer (23). In the present study, we found that the optimal threshold for SCC was 40 s/mm 2 and 100 s/mm 2 for adenocarcinoma, which was similar to a previous report (20).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the multistep estimation process of estimating IVIM parameters, the choice of b-value threshold in the initial estimation of the pure diffusion coefficient (D) and perfusion fraction (f) affects the final fitting (19,20). Furthermore, the optimal b-value distribution (BVD) and choice of the b-value threshold are organ-specific (19)(20)(21)(22)(23).…”
Section: In Vivomentioning
confidence: 99%
“…Optimal choices of b‐values and the number of repeated acquisitions of each b‐value have been studied extensively for the monoexponential diffusion model, mainly using error propagation or similar techniques . Some studies have performed similar work with the IVIM model . However, these studies on the IVIM model have focused on minimizing the error of parameters estimated simultaneously from the biexponential model and not the segmented procedure nor for estimation of only D and f .…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Some studies have performed similar work with the IVIM model. 9,[20][21][22][23][24] However, these studies on the IVIM model have focused on minimizing the error of parameters estimated simultaneously from the biexponential model and not the segmented procedure nor for estimation of only D and f. Optimization of acquisition of data for segmented model fitting is to our knowledge hitherto limited to choice of intermediate b-value in three-b-value protocols. 11,25 The aim of this work was to develop a framework for optimization of b-value schemes for diffusion-weighted imaging data used to estimate IVIM parameters D and f with segmented model fitting.…”
mentioning
confidence: 99%